SEX EDUCATION IN THE CONTEXT OF INDONESIAN EARLY CHILDHOOD - Chairilsyah, Daviq (International Journal of Educational Best Practices, 2019)
Indonesia is a country that is experiencing a crisis of child abuse and sexual violence. Data from 2015 to 2019 shows a significant increase in this problem. KPAI data states that the culprit is the closest person to the child such as stepfather and biological, closest family, and colleague. When our children ask about their sexuality, we will be moved quickly. This attitudes like that mean wrong, because children have a curiosity about many things, if we as parents cannot direct properly, cannot provide clear information they tend to look for information from others and their friends, the information is not necessarily good. Very few people, especially parents who care about sex education and place sex as something important. Even many parents who do not provide sex education to children, with the reason the child will know it by itself. During this time, the idea of sex is belonging to adults only, so discussing the problem of sex in children is not easy. However, teaching sex education to children must be given so that children do not go wrong in their lives. The purpose of sex education in early childhood is to provide an adequate understanding of physical, mental, and emotional maturity processes, reducing fear and anxiety related to sexual adjustment and development. Sex education is given starting from the age of five, age 1-5 years, age 5-10 years, age before adolescence, adolescence. How to educate young children about sex through family, environment, and education at school.